Level Design : Processes and experiences - Totten, Christopher W., ....- (CRC Press : Florida, 2017)
In this book, veteran game developers, academics, journalists, and other provide their processes and experiences with level design. Each provides a unique perspective representing multiple steps of the process for interacting with and creating game levels - experiencing levels, designing levels, constructing levels, and testing levels. These diverse perspectives offer readers a window into the thought processes that result in memorable open game worlds, chilling horror environments, computer-generated levels, evocative soundscapes, and many other types of gamespaces. This collection invites readers into the minds of professional designers as they work and provides evergreen topics on level design and game criticism to inspire both new and veteran designers.
Keywords: Games; Programmeren